(untitled) - De Beer, Janke

Pyranometers vs. Spectrometers: modelling the effects of a changing solar spectrum on the yield of bifacial PV modules (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng) -- Stellenbosch University, 2022.